2022
DOI: 10.3390/nano12050857
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Characterization of Doxycycline-Loaded Polymeric Nanoparticles for Testing Antitumor/Antiangiogenic Action in Experimental Colon Cancer in Mice

Abstract: Nanotherapeutics can enhance the characteristics of drugs, such as rapid systemic clearance and systemic toxicities. Polymeric nanoparticles (PRNPs) depend on dispersion of a drug in an amorphous state in a polymer matrix. PRNPs are capable of delivering drugs and improving their safety. The primary goal of this study is to formulate doxycycline-loaded PRNPs by applying the nanoprecipitation method. Eudragit S100 (ES100) (for DOX-PRNP1) and hydroxypropyl methyl cellulose phthalate HP55 (for DOX-PRNP2) were tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“…Therefore, reducing the IFP by normalizing the vasculature is key to enhancing the efficacy of chemotherapy [5]. Some current studies are using nanocarriers to achieve the combined application of antivascular drugs and chemotherapeutic drugs [72,[78][79][80][81][82][83][84]. It has been reported that moderate-dose anti-angiogenic drugs can kill small nonfunctional blood vessels to normalize the tumor vasculature, resulting in increased the accumulation of and penetration by the chemotherapeutic drug and a significant improvement in the oxygen concentration within solid tumors [85].…”
Section: Chemotherapymentioning
confidence: 99%
“…Therefore, reducing the IFP by normalizing the vasculature is key to enhancing the efficacy of chemotherapy [5]. Some current studies are using nanocarriers to achieve the combined application of antivascular drugs and chemotherapeutic drugs [72,[78][79][80][81][82][83][84]. It has been reported that moderate-dose anti-angiogenic drugs can kill small nonfunctional blood vessels to normalize the tumor vasculature, resulting in increased the accumulation of and penetration by the chemotherapeutic drug and a significant improvement in the oxygen concentration within solid tumors [85].…”
Section: Chemotherapymentioning
confidence: 99%
“…The common treatment for breast cancer involves surgery, radiation therapy, chemotherapy, hormone therapy, and targeted therapy. Recently, novel anticancer agents have been identified among numerous antibiotics [ 6 , 7 , 8 , 9 ]. It has been found that antibiotics (actinomycin, monensin, ivermectin, doxycycline, and salinomycin) could also have synergistic anti-tumor effects by inhibiting anti-apoptotic proteins and proteins involved in angiogenesis and migration of tumor cells [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticle-mediated delivery of drugs is a promising approach for cancer treatment that involves the use of nanomaterials to deliver drugs directly to cancer cells while reducing damage to healthy cells. Doxycycline conjugated with or loaded into polymeric, metallic, or liposome nanoparticles has shown considerable antitumor effects on various types of cancer cells [ 7 , 12 , 16 , 17 , 18 ]. Copper nanoparticles conjugated with doxycycline showed excellent antitumor effects on HeLa and HepG2 cells in a synergistic manner [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dox is a broad-spectrum antibiotic belonging to the tetracycline class, usually used in the management and treatment of various infections caused by Gram-positive and Gram-negative bacteria, rickettsiae, chlamydiae, spirochetes, mycoplasmas, and protozoans [23,24]. Compared with other tetracyclines, doxycycline has a better absorption profile, longer half-life, safety profile, and excellent efficacity for susceptible microorganisms, even at lower concentrations [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other tetracyclines, doxycycline has a better absorption profile, longer half-life, safety profile, and excellent efficacity for susceptible microorganisms, even at lower concentrations [25,26]. Doxycycline monohydrate and doxycycline hyclate are equally effective, but doxycycline hyclate is more frequently uwatersed in pharmaceutical samples due to its good water solubility [24]. Amoxicillin (Amox) Doxycycline (Dox)…”
Section: Introductionmentioning
confidence: 99%